Improving the Economic Capacity of Village Communities in KKN PPM Programme - Yulia, Lia; Rahman, Nandang Fauzi; Kasman, Kasman; Febrianti, Seli Belinda (Indonesian Journal of Advanced Social Works, 2023)
Tanjungsari Village is one of the 8 villages in Sadananya District, Ciamis Regency. The problems found include several aspects including optimization and escalation of tourism villages, adding the selling value of a product, legality of MSMEs, upgrading the Women Farmers Group (KWT). The implementation of KKN-PPM in Tanjungsari Village, Sadananya District from August 1 to September 1, 2023. In the implementation of KKN-PPM, there are several implementation methods used, namely the survey method, mentoring method, lecture method, guidance method, and promotion method. In general, physical and non-physical activities, main work programs and additional work programs have been well realized so that they reach the ultimate goal of the work program and each work program implemented gets a good response from the community and village officials.